The Size of the Universe - Cardinale, Joseph (Book collections on Project MUSE., 2010)
The landscape of this novel in stories--Joseph Cardinale's first book-length work of fiction--is as familiar as childhood yet beguilingly surreal. The question of whether or not the child in the first fiction and the man in the last story are the same person--and whether any person is the same from one moment to the next--is perhaps the book's main question. In prose as spare as it is meticulous, The Size of the Universe conjures an elegant labyrinth of time, space, and memory, in which a wavering self, a self on the verge of becoming nothing, seeks a safe haven from the throes of near-reli.